“Sticky Business”: An Examination of Female Musicians in the Context of Perth’s Metal Community - Glitsos, Laura (Taylor and Francis, 2019)
This study investigates and elaborates on the experiences of female musicians in the Perth metal music community, which has traditionally been identified as a male-dominated environment and even a hypermasculine space. This study serves to inform the growing research emerging from metal music studies and to contribute to the wider conversation about women’s experiences in male-dominated fields. To undertake this research, I used a mixed-methods approach that includes a survey questionnaire of thirteen women who have all identified as musicians interacting within the Perth metal community and one extended interview with a veteran metal guitarist.